Evaluation of the cone beam CT for internal target volume localization in lung stereotactic radiotherapy in comparison with 4D MIP images. Issue 11 (8th October 2013) - Wang, Lu; Chen, Xiaoming; Lin, Mu‐Han; Xue, Jun; Lin, Teh; Fan, Jiajin; Jin, Lihui; Ma, Charlie M.
Abstract : Purpose: : To investigate whether the three‐dimensional cone‐beam CT (CBCT) is clinically equivalent to the four‐dimensional computed tomography (4DCT) maximum intensity projection (MIP) reconstructed images for internal target volume (ITV) localization in image‐guided lung stereotactic radiotherapy. Methods: : A ball‐shaped polystyrene phantom with built‐in cube, sphere, and cone of known volumes was attached to a motor‐driven platform, which simulates a sinusoidal movement with changeable motion amplitude and frequency. Target motion was simulated in the patient in a superior‐inferior (S‐I) direction with three motion periods and 2 cm peak‐to‐peak amplitudes. The Varian onboard Exact‐Arms kV CBCT system and the GE LightSpeed four‐slice CT integrated with the respiratory‐position‐management 4DCT scanner were used to scan the moving phantom. MIP images were generated from the 4DCT images. The clinical equivalence of the two sets of images was evaluated by comparing the extreme locations of the moving objects along the motion direction, the centroid position of the ITV, and the ITV volumes that were contoured automatically by Velocity or calculated with an imaging gradient method. The authors compared the ITV volumes determined by the above methods with those theoretically predicted by taking into account the physical object dimensions and the motion amplitudes. The extreme locations were determined by the gradient method along the S‐I axis through the center of the object. The centroid positions were determined by autocenter functions. The effect of motion period on the volume sizes was also studied. Results: : It was found that the extreme locations of the objects determined from the two image modalities agreed with each other satisfactorily. They were not affected by the motion period. The average difference between the two modalities in the extreme locations was 0.68% for the cube, 1.35% for the sphere, and 0.5% for the cone, respectively. The maximum difference in the centroid position of the cylinder, sphere, and cone was less than 1.4 mm between the two modalities for all motion periods studied. For the ITV volume evaluation, the authors found that both MIP‐based and CBCT‐based ITVs increased with increases of motion period. Furthermore, the MIP‐based ITV volumes were generally larger than those determined from the CBCT images, with the difference in autocontoured volumes being 2.57%, 1.66%, and 1.82% for the sphere, cylinder, and cone, respectively, while these differences increased to 9.57%, 3.52%, 8.71% for the above objects when the gradient method was used. The authors found that the autocontour method was accurate enough to predict the actual ITV values with the absolute differences less than 2.4% comparing to the theoretically predicted values. Conclusions: : The extreme location and the centroid position of the objects agree with each other between the two image modalities when the breathing motion is sinusoidal. Although the ITV volumes delineated from both image modalities changed with the motion period, the differences in ITV between the two modalities were minimal when an optimized window level was used. The authors' results suggest that CBCT and MIP images are equivalent in determining an ITVˈs position in the conditions studied. The CBCT is adequate in providing imaging‐guidance for lung cancer treatment.